Maximally Orthogonalized Higher Order Basis Functions in Large-Domain Finite Element Modeling in Electromagnetics - Savic, Slobodan V.; Ilic, Milan M.; Kolundzija, Branko M. (IEEE transactions on antennas and propagation, 2020)
Curl-conforming max-ortho basis functions (MOBFs) are coupled with higher order large-domain curved finite elements (FEs). The performance of the functions is compared with that of the classical and near-ortho basis functions. Through numerical experiments, it is shown that max-ortho FEs yield highly orthogonal mass matrices, for practically arbitrarily high orders of polynomial field approximations. This facilitates the usage of iterative solvers and it significantly increases their efficiency. Accurate and fast computation of MOBFs, of arbitrarily high orders, is enabled by the proposed two-term recurrent formula.